2004
DOI: 10.1159/000076237
|View full text |Cite
|
Sign up to set email alerts
|

24-Hour Electrocardiogram before and during Cisapride Treatment in Neonates and Infants

Abstract: We studied prospectively the effects of cisapride on heart rate and rhythm using standard ECG and 24-hour ECG recordings in term and preterm neonates and infants. We studied subjects with gastroesophageal reflux disease (apparent life-threatening events, apneas, bradycardias) before and 3 days after starting cisapride (0.8 mg/kg/day in 4 doses). We performed standard ECGs for determination of corrected Q-T interval (QTc) and Q-T dispersion (QTd) and 24-hour ECG recordings for analysis of heart rate, heart rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Semama et al [ 46 ] (only term infants) and Zamora et al [ 47 ] (preterm and term infants) both published a study in 2001 with similar findings of longer QTc intervals after starting cisapride (dose ≤ 1 mg/kg/day). Zamora et al [ 48 ] subsequently published another study, to confirm a significant longer QTc interval in preterm infants whereas no significant differences were observed for term infants. Chhina et al [ 49 ] also detected a longer QTc interval after cisapride administration.…”
Section: Resultsmentioning
confidence: 99%
“…Semama et al [ 46 ] (only term infants) and Zamora et al [ 47 ] (preterm and term infants) both published a study in 2001 with similar findings of longer QTc intervals after starting cisapride (dose ≤ 1 mg/kg/day). Zamora et al [ 48 ] subsequently published another study, to confirm a significant longer QTc interval in preterm infants whereas no significant differences were observed for term infants. Chhina et al [ 49 ] also detected a longer QTc interval after cisapride administration.…”
Section: Resultsmentioning
confidence: 99%
“…Of the three articles analysed in this systematic review, only Djeddi et al showed significant longer QTc in infants >32 weeks GA [59]. Next to cisapride [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58]74,75] and domperidone [59][60][61]73,75], doxapram has also been studied because of its presumably presence of adverse cardiac effects such as second-degree AV-block and longer QTc intervals. Doxapram hydrochloride is a powerful respiratory stimulant used for idiopathic apnea of prematurity unresponsive to methylxanthines.…”
Section: Discussionmentioning
confidence: 99%
“…Khogphatthanayothin (dose ≤1 mg/kg/day) [46,47]. Zamora et al subsequently published another study, to confirm a significant longer QTc interval in preterm infants whereas no significant differences were observed for term infants [48]. Chhina et al also detected a longer QTc interval after cisapride administration.…”
Section: Cisapridementioning
confidence: 99%
“…There are reports on QTc interval prolongation assessment for medications known to affect the QTc interval in adults during exposure in neonates. Cisapride prolonged the QTc interval in preterm and term neonates by +20 ms [ 30 , 31 ], while—in contrast to adults—domperidone showed no effect on the mean QTc interval [ 32 ]. It remains difficult to put this into perspective, especially for pharmacovigilance in the first week of life, because of maturational and non-maturational factors ( Table 1 ) [ 13 , 14 , 15 , 16 , 17 , 18 , 24 ].…”
Section: Discussionmentioning
confidence: 99%